Direct and antibody dependent cell mediated cytotoxicity against Giardia lamblia by splenic and intestinal lymphoid cells in mice. (January 1986) - Kanwar, S S; Ganguly, N K; Walia, B N; Mahajan, R C
Abstract : Direct cytotoxicity and antibody dependent cell mediated cytotoxicity against Giardia lamblia trophozoites exhibited by splenic, intraepithelial and lamina propria lymphocyte populations isolated from G lamblia infected mice were studied. Different patterns of cytotoxicity were found. Intraepithelial lymphocytes showed a direct cytotoxic activity of 20.6 +/- 5.6% before infection. It was significantly higher on the 20th (p less than 0.01) and 30th (p less than 0.05) day postinfection. Lamina propria lymphocytes showed a significantly augmented level of both direct cytotoxicity and antibody dependent cell mediated cytotoxicity on the 20th and 30th postinfection days. Direct cytotoxicity by splenic lymphocytes remained unchanged during infection but antibody dependent cell mediated cytotoxicity was significantly increased.